THE INNOVATIVE CONTROL OF THE HEATING UP PROCESS OF THE METAL IN THE FURNACE USING SPATIAL ELECTRIC FIELD - Kachan, Y. G.; Yerofieieva, A. A. (Radio Electronics, Computer Science, Control, 2018)
Context. The actual task of developing an innovative control system for the process of metal heating up in the chamber furnace has been solved in the work. Objective is a creation of an algorithm for the controlling of the heating up of the metal with additional use as the controlling influence of a spatial electric field in the furnace chamber. Method. A regression model of a real chamber furnace was obtained using well-known experimental design techniques. The model is the basis of the algorithm and takes into account the magnitude of the voltage between the burner and the metal cage. Results. A control system for the chamber furnace has been developed, in which the optimal values of control actions at each step of the heating cycle are determined according to the created algorithm. The proposed control system is universal, it gives the dynamics of the change in the constant voltage and the gas supply in steps in time j to perform any given mode of heat treatment of the metal. The carried out experiments on a real chamber furnace with a withdrawable hearth at OOO «Zaporizhzhya Titanium and Magnesium Plant» have confirmed this. Analysis of the obtained graphs of the annealing temperature of the metal. There is a high uniformity and a better quality of metal heating when implementing the optimal values of control actions obtained with the help of the algorithm. The dynamics of gas consumption by the chamber furnace during the heating cycle is shown in accordance with the optimization performed without the supply of voltage and with the supply of voltage. The obtained data testify to the possibility of a significant increase in the energy efficiency of the furnaces in question. Conclusions. For the first time, the possibility and efficiency of using a spatial electric field in the furnace chamber as a control action has been proved, which confirms the scientific novelty of the results obtained. The developed control algorithm is universal from the viewpoint of thermal treatment of metal and can be used in chamber furnaces of any industrial enterprise. During one heating cycle, natural gas consumption is reduced by more than 10%, which confirms the practical importance of research.